2018
DOI: 10.1016/j.cobme.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Temporal pattern of electrical stimulation is a new dimension of therapeutic innovation

Abstract: Artificial activation of the nervous system requires selection of appropriate stimulation parameters including stimulation amplitude, stimulation pulse duration, and stimulation pulse repetition rate. The temporal pattern of stimulation, i.e., the timing between stimulation pulses, is a novel dimension of stimulation parameter tuning. The effects evoked by artificial activation of the nervous system are dependent on the pattern of stimulation, and different patterns of stimulation, even when delivered at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…Neuronal representation of sensory information is highly complex (Lieber & Bensmaia, 2019), and the ability to selectively recruit neuronal populations proximal to the electrode by varying pulse amplitude, frequency, or polarity could provide the ability to stimulate neural activity that matches physiological response patterns (Anderson, Duffley, Vorwerk, Dorval, & Butson, 2018; Cai et al., 2017; Delhaye, Saal, & Bensmaia, 2016; Grill, 2018; Histed, Bonin, & Reid, 2009; Hofmann, Ebert, Tass, & Hauptmann, 2011; Koivuniemi & Otto, 2011; Kuncel & Grill, 2004; Macherey, van Wieringen, Carlyon, Deeks, & Wouters, 2006; McIntyre & Grill, 2000, 2002; McIntyre, Richardson, & Grill, 2002; Michelson, Eles, Vazquez, Ludwig, & Kozai, 2019). For example, neuronal adaptation is a common response to sustained stimuli and is believed to allow the brain to better respond to transient stimuli (Wark, Lundstrom, & Fairhall, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal representation of sensory information is highly complex (Lieber & Bensmaia, 2019), and the ability to selectively recruit neuronal populations proximal to the electrode by varying pulse amplitude, frequency, or polarity could provide the ability to stimulate neural activity that matches physiological response patterns (Anderson, Duffley, Vorwerk, Dorval, & Butson, 2018; Cai et al., 2017; Delhaye, Saal, & Bensmaia, 2016; Grill, 2018; Histed, Bonin, & Reid, 2009; Hofmann, Ebert, Tass, & Hauptmann, 2011; Koivuniemi & Otto, 2011; Kuncel & Grill, 2004; Macherey, van Wieringen, Carlyon, Deeks, & Wouters, 2006; McIntyre & Grill, 2000, 2002; McIntyre, Richardson, & Grill, 2002; Michelson, Eles, Vazquez, Ludwig, & Kozai, 2019). For example, neuronal adaptation is a common response to sustained stimuli and is believed to allow the brain to better respond to transient stimuli (Wark, Lundstrom, & Fairhall, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This stands in contrast to the mean spike rate or periodicity code that are often proposed to be neural codes for frequency perception in higher neural centres [6][7][8][9]. Electrical burst stimulation has been suggested to be useful in restoring the sense of touch in amputees using a prosthesis [10][11][12] or in the treatment of movement disorders through deep brain stimulation [13][14][15]. These studies were generally concerned with the efficacy of inducing neural activity, rather than the effect of burst stimulation on information encoding.…”
Section: Introductionmentioning
confidence: 99%
“…The application of other biomarkers or multiple biomarkers in the design of closed-loop stimulation for PD is worth exploring (Hoang et al, 2017). The controller regulated the stimulation frequency, but the effects of DBS are also dependent on the pulse amplitude, pulse duration, and stimulation pattern (Kuncel and Grill, 2004; Grill, 2018). Further, Holt et al demonstrated that the effects of burst DBS in a network model of the basal ganglia (Hahn and McIntyre, 2010) were strongly dependent on timing relative to the phase of oscillatory activity (Holt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%